2006
DOI: 10.4269/ajtmh.2006.74.120
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Rickettsia Felis in Ctenocephalides Felis Fleas Parasitizing Rats in Cyprus

Abstract: Rickettsia felis was identified by polymerase chain reaction amplification and DNA sequencing analysis in Ctenocephalides felis fleas parasitizing rats in Cyprus. Murine typhus caused by R. typhi was believed to be the only flea-transmitted rickettsiosis on the island. This is the first report of this pathogen in southeastern Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…Our results confirm R. typhi in a known flea vector of murine typhus in a highly disease-endemic region of East Java, Indonesia (11,13). R. felis has been shown to infect fleas of peridomestic rodents (7,8) and fleas other than C. felis (1,5,14). However our report is the first of R. felis naturally infecting X. cheopis fleas, a vector of plague and murine typhus.…”
Section: Discussionsupporting
confidence: 71%
“…Our results confirm R. typhi in a known flea vector of murine typhus in a highly disease-endemic region of East Java, Indonesia (11,13). R. felis has been shown to infect fleas of peridomestic rodents (7,8) and fleas other than C. felis (1,5,14). However our report is the first of R. felis naturally infecting X. cheopis fleas, a vector of plague and murine typhus.…”
Section: Discussionsupporting
confidence: 71%
“…The biology of these species is not well known in Korea and may reflect host and/or ectoparasite reproductive seasonal differences. The PCR techniques used in our study for detection of R. typhi (Webb et al, 1990) have been used for identifying Rickettsia pathogens in the cat flea, Ctenocephalides felis, from various countries throughout the world, including Cyprus (Psaroulaki et al, 2006), Mexico (Zavala-Castro et al, 2005), Peru (Blair et al, 2004), Afghanistan (Marie et al, 2006), USA (Reeves et al, 2005), and Israel (Bauer et al, 2006). Positive pools found in this study were observed from fleas taken only from A. agrarius that were negative by IFA for R. typhi.…”
Section: Discussionmentioning
confidence: 99%
“…typhi had been considered to be the only fleaborne rickettsiosis present in Cyprus until 2006, when R. felis was detected in C. felis . 16 We report molecular detection and identification of R. typhi in X. cheopis and L. segnis collected from rats in Cyprus and the occurrence of R. felis in X. cheopis .…”
Section: Discussionmentioning
confidence: 99%
“…4 However, the only recognized vector is the cat flea. 8 Other flea species such as C. canis , [17][18][19] Anomiopsyllus nudata , 20 Archaeopsylla erinacei , 16,21,22 Ctenophthalmus sp., 21 X. cheopis , 22,23 Pulex irritans , 18 and ticks and mites 8 have been implicated as alternative competent vectors of R . felis .…”
Section: Discussionmentioning
confidence: 99%